Joged Bumbung; tradition or transgression? - Eka Ari Suhendra (Bali Tourism Journal, 2018)
Balinese dance, mystically terrific yet stunningly captivating at the same time. Balinese divides the art of dance into three types namely The Wali (Sacred Dance), The Bebali, and The Balih Balihan (Performing Dance). Joged Bumbung, one of Balih balihan dance, acts as social dance as well as entertainment. However, Recent occasion took place in November 2017 sparked netizen’s critic about erotic joged performance video on Les Village, Singaraja. Culturalists feared it would ignite the reaction of many parties, for instance, the UNESCO. In addition, erotic joged violates ethics and is a form of cultural defamation thus it is essential to establish pararem to prevent similar incidents in the future.